2015
DOI: 10.1590/1982-0194201500051
|View full text |Cite
|
Sign up to set email alerts
|

Análise da tendência das taxas de internações por pneumonia bacteriana em crianças e adolescentes

Abstract: Objective: To analyze distribution and tendency of hospital admissions rates for bacterial pneumonia in children and adolescents. Methods: This ecological, time series study included secondary data obtained from the Hospital Information System of the SUS. We calculated hospital admission coefficients for 10,000 inhabitants triennially. For the analysis of tendency, a model of polynomial regression was used. Results: Most hospital admissions occurred in the East health macro-region between the second and fourth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
1
5
0
2
Order By: Relevance
“…Therefore, our conclusions cannot be completely generalized to the private health system. On the other hand, the mean age of the patients included in this study is similar to those described in other publications on the global impact of RIs in children, as well as the predominance of boys, making our findings fairly generalizable [14,22,23].…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, our conclusions cannot be completely generalized to the private health system. On the other hand, the mean age of the patients included in this study is similar to those described in other publications on the global impact of RIs in children, as well as the predominance of boys, making our findings fairly generalizable [14,22,23].…”
Section: Discussionsupporting
confidence: 86%
“…Data from an ecological study of pneumonia hospitalizations in children and adolescents living in the neighboring state of Paraná in relation to the period 2000-2011 describe the occurrence of 2,295,780 hospitalizations of children and adolescents, 59,028 (2.57%) of which were due to bacterial pneumonia. 16 In view of the need to integrate different aspects related to measuring the impact of introducing a vaccine in a specific region, the objective of this article is to describe the impact of PCV10 on pneumonia hospitalizations of children under 5 years old in the state of Santa Catarina, Brazil, between 2006 and 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mothers of the study reported that they were able to breastfeed up to six months of the baby's life, a fact recognized as a reducing factor of the hospital admission rate (16) , there was an association between the Longitudinality feature and the period of Exclusive Breastfeeding from two to four months, coinciding with the period when many women returned to work. This moment may raise in the mothers a greater demand for health services, in an attempt to provide, before returning to work, good health care for their babies.…”
Section: Discussionmentioning
confidence: 80%